Botswana : 2013 Article IV Consultation. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2013)
This paper discusses 2013 Article IV Consultation highlights slower economic performance and financial risks in Botswana. The output growth is expected to remain broadly unchanged in 2013 as strong nonmining sector growth would offset the subdued mining output. Banks' high exposure to households and the acceleration in the growth of unsecured lending are, however, potential vulnerabilities. The authorities are advised to continue to bolster their surveillance capacity to monitor financial sector developments and consider implementing macroprudential measures to temper the rate of growth of household borrowing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet